The Effect of Slack Resources on Innovation Performance and the Environmental Adaptability of Public Hospitals: The Empirical Evidence From Beijing of China - Lu, Wei; Song, Xinrui; Hou, Changmin; Zhu, Junli (Frontiers in Public Health, 2022)
Background: The development level of public hospitals has a direct impact on people's health. The reform of the medical industry in China has been gradually underway in recent years, while hospitals face a complex and uncertain environment. This study aims to explore the mechanism of resources slack in buffering environmental uncertainty and promoting innovation in public hospitals. Methods Based on previous literature related to environmental adaptability, resources slack, and innovation performance, this study has conducted a literature review and has established a study framework. A questionnaire survey has been conducted among clinicians in representative tertiary public hospitals in Beijing. A total of 318 valid data have been eventually obtained, while regression models have been used to analyze the data. Results Innovation performance has played a mediating role in the impact of both resources slack and its three dimensions on environmental adaptability of public hospitals. Among them, there has been a complete mediating effect for time slack, while there has been a partial mediating effect for staff and space dimensions. Conclusion This study found that resources slack in public hospitals can improve environmental adaptability by affecting innovation performance. It is necessary for public hospitals to reserve resources slack to ensure that there is sufficient condition for innovation in the face of uncertain changes.